PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) MELALUI ANALISIS 5W UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK DAN MEMAHAMI ISI PERCAKAPAN PADA MATA PELAJARAN BAHASA INDONESIA - Yuhanith Zamaruda; Dede Nuraida; Ngunarti (STKIP Subang, 2026)
Listening proficiency is a language skill that elementary school students need to master, as it plays a crucial role in comprehending orally conveyed information. Preliminary observations in Class III B at UPT SD Negeri Kebonsari 3 Tuban revealed that the majority of students struggled to identify key information and understand the content of conversations. This study aimed to improve students' listening skills and their ability to comprehend conversation content by implementing the Problem-Based Learning (PBL) model combined with 5W analysis (What, Who, When, Where, and Why). The study employed the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, conducted over two cycles. Each cycle comprised the stages of planning, action, observation, and reflection. Data were collected through observation, tests, and documentation, and subsequently analyzed using both quantitative and qualitative descriptive approaches. The results demonstrated an improvement in listening skills and conversation comprehension across the cycles. Learning mastery increased from 44% in the pre-action stage to 76% in Cycle I, reaching 100% in Cycle II. The students' average scores also rose from 62.52 to 73.00, and subsequently to 83.76. Beyond student achievement, teacher and student activities during instruction also showed positive development. These findings indicate that the implementation of the Problem-Based Learning model combined with 5W analysis serves as an effective instructional alternative, helping students comprehend oral information more systematically while simultaneously enhancing their listening skills in Indonesian language lessons at the elementary school level.